Mechanism to continue system availability during cyber threat scenario - Safdar, S. (Association for Computing Machinery, Inc, 2017)
It is known that cyber attacks on the application systems causes denial of services to avoid confidentiality and integrity compromise. The system remains inaccessible until it is completely recovered from that threat. This unavailability of the system is very important to handle as it results in huge monetary loss for organizations and their customers suffer with bad quality services. The main research objective is to design a framework for sustaining the system's availability at application level during the period of cyber attack. A designed framework is comprised of two compon en ts th at propose on e of the poten tial solution s for handling the system's unavailability problem while it is under attack. Ad hoc data migration is the first component that transfers the information to the alternative system's data storage when the attack is detected. Secured authentication is another very important component that compliments the alternatively available system to provide the secured information services to the end user. Secured authentication is designed differently with more strength compared to the conventional textual password authentication scheme so that the malicious users can be restricted from accessing the alternatively available system. © 2017 ACM.